Conversation Analytic Language Teacher Education in Digital Spaces - Balaman, Ufuk. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book presents original research into language teacher education (LTE) activities in digital spaces, making use of a multimodal Conversation Analysis (CA) approach to examine multiple datasets and bring new insights into the theory, research, and practice of second/foreign language teacher education. The author conceptualizes a model of Conversation Analytic Language Teacher Education (CALTE), proposing a new knowledge base for LTE, identifying research-informed defining features, mapping the scope of an original praxis base, and providing research evidence from the implementation of this approach in and for digital spaces. The result is an argument for wide implementation and on-going improvement of the CALTE approach, and the book will be of interest to language teacher education professionals, multimodal CA researchers, and applied linguists. Ufuk Balaman is Associate Professor of Applied Linguistics in the Department of English Language Teaching and Director of (HUMAN) Micro-Analysis, Social Interaction, and Learning Research Centre at Hacettepe University, Turkey. .
Chapter 1. Introduction -- Chapter 2. Conceptualizing Conversation Analytic Language Teacher Education -- Chapter 3. Pre-Service Teacher Learning in Video-Mediated Peer Interactions -- Chapter 4. Reflective Talk in Video-Mediated Post-Observation Conversations -- Chapter 5. Design, Feedback, and Reflection for Video-Mediated L2 Interactions -- Chapter 6. Translocating Language Teacher Education: The Way Forward.
Keywords: Language and languages-Study and teaching; Teachers-Training of; Digital media; Virtual reality; Augmented reality; Language Teaching and Learning; Language Education; Teaching and Teacher Education; Digital and New Media; Virtual and Augmented Reality